ANALYZING THE CORE OF HUMANITY: INSIGHTS GAINED FROM DOGVILLE - Wilson , Henry T. J. (International Research Journal of Sociology, Psychology and Anthropology, 2024)
Lars Von Trier, the acclaimed filmmaker, has challenged and redefined the art of cinema through his distinctive and provocative films. This article explores how Von Trier's work, including his groundbreaking film "Dogville," has reshaped cinematic conventions and aesthetic experiences. By examining his evolution from earlier works like "Breaking the Waves" to more recent productions such as "Melancholia" and "Nymphomaniac," we see a consistent thread of originality and reflection on the film industry. "Dogville" marked a significant turning point, inaugurating a unique paradigm for film production and transforming the viewer's aesthetic experience. Von Trier's films deconstruct conventions and copyright conditions, offering new artistic and cinematic possibilities while challenging traditional cinematic philosophy. This article delves into the impact of Von Trier's work on the American film industry and how it has influenced the way we perceive art and cinema.